A simple storage chair / Muhamad Basri Md Daud, Norashikin Kamarudin and Asnawi Seraila - Md Daud, Muhamad Basri; Kamarudin, Norashikin; Seraila, Asnawi (2014)
This research was handled to investigate the suitability of blockboard as a material for chair production using a simple design. The chair was produced, and the data were collected via survey form. The data were analyzed using SPSS based on the questionnaire that had been distributed to 150 correspondents, 80% of the correspondents give the positive response to the material used, simple design, friendly user, suitability of the product to everyone and marketable of the product. The idea of producing a simple storage chair will meet customer satisfaction and acceptable in market demand.